Populus ciliata mediated synthesis of copper oxide nanoparticles for potential biological applications. (22nd February 2019) - Hafeez, Muhammad; Arshad, Rabia; Khan, Jahanzeb; Akram, Bilal; Ahmad, Muhammad Naeem; Hameed, Muhammad Usman; Haq, Sirajul
Abstract: The copper oxide nanoparticles (CuO NPs) have been successfully synthesized using the leaf extract of Populus ciliata (P. ciliata) as capping and stabilizing agent. The crystalline nature of CuO NPs was confirmed by x-ray diffraction (XRD) while the morphological study was conducted by performing Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM). The percent composition and purity was examined by using energy dispersive x-ray (EDX) while fourier transform infrared (FTIR) spectroscopy was used to study surface functional groups. The copper oxide nanoparticles (CuO NPs) were tested against Gram positive bacteria; Staphylococcus aureus (S. aureus) Staphylococcus pyogenes (S. aureus) and Gram negative bacteria; Escherichia coli (E. coli), Pseudomonas aeruginosa (P. aeruginosa) and Klebsiella pneumoniae (K. pneumoniae) for its antibacterial activity. The antibacterial activity was increased with increasing concentration of the CuO NPs. A higher activity was found against Gram negative bacteria as compared to Gram positive bacteria.